Evaluating Neutrophil-to-albumin ratio Association with Clinical Outcomes in Acute Pancreatitis: A MIMIC-IV Based Retrospective Study - XU, CHAO; LIYANG, WAN; LIMIN, LIMIN; ZHAO, CHEN-LIANG (Pakistan Journal of Medical & Health Sciences, 2025)
Background: The Neutrophil-to-albumin ratio (NPAR), a novel inflammatory-nutritional composite index, has recently demonstrated prognostic utility across various pathological conditions. The relationship between NPAR and the severity or mortality of acute pancreatitis (AP) remains unclear, despite the increasing clinical importance of this condition. Aim: To evaluate the relationship between NPAR levels and 28-day mortality outcomes among hospitalized acute pancreatitis patients. Methods: This retrospective cohort study utilized the Medical Information Mart for Intensive Care IV (MIMIC-IV) database to evaluate how well NPAR predicts outcomes in acute pancreatitis. The key endpoint was mortality within 28 days, analyzed using multivariable Cox regression to evaluate the independent prognostic importance of NPAR after controlling for significant covariates. Stratified analyses further explored whether this relationship remained robust across clinically relevant subpopulations. Results: Multivariable Cox regression analysis of 474 eligible acute pancreatitis patients, adjusted for age, sex, race, and comorbidities, demonstrated a significant dose-dependent association between elevated NPAR levels and 28-day all-cause mortality. Compared to the low- NPAR reference group (<25), patients in the intermediate-NPAR group (25-30.9) exhibited a 1.1-fold increased mortality risk (adjusted HR: 2.1; 95% CI: 1.1-4.02; p=0.025), while those in the high NPAR group (≥31) showed a 1.2-fold higher risk (adjusted HR: 2.2; 95% CI: 1.19-4.1; p=0.012). Kaplan-Meier analysis revealed significantly different survival curves among NPAR groups (log-rank p=0.037), with the highest NPAR group showing the poorest survival. Conclusions: NPAR may serve as a novel prognostic biomarker for acute pancreatitis, although its clinical applicability still needs to be validated in a large number of prospective multicenter studies